Program Habituasi Membaca Asma’ul Husna Berbasis Media Pembelajaran Audio Visual terhadap Anak Usia Dini - Utama, Ferdian; Irhamudin; Linawati (Wisanggeni: Jurnal Pengabdian Masyarakat, 2022)
Character is needed in every individual, especially good character. Creating a good personality can be done in three educational environments: education in the family, school, and community. Effectively, cultivating good character in a person can be through habituation and starting in early childhood education. This service is to create a good character from an early age, namely through reading Asmaul Husna and translating into Indonesian and English. The method in this service uses the ABCD (Asset Base Community Development) method, the location of the service is carried out at the Ma'arif NU Metro Lampung early childhood education institution, which consists of three schools, namely RA Ma'arif, TK Maarif 1, and TK Ma'arif 2 Metro Lampung. As with the Service Locations that will be carried out later, the habituation program is based on the values of ASWAJA and Nahdliyah. However, its application requires innovation from audio-visual media.